Prevalence and patterns of maxillofacial trauma: a retrospective descriptive study - Ammar Al-Hassani (14150046) (2019)
Introduction We aimed to describe the prevalence and pattern of maxillofacial trauma in Qatar. Methods This is a retrospective study of trauma registry data at Hamad General Hospital during the period from January 2011 to December 2014. The study included all traumatic maxillofacial patients who underwent CT scan and were admitted during the study period. Results A total of 1187 patients with maxillofacial injuries were included in the study and 18.5% of all trauma admissions were related to maxillofacial injuries. Young age and males were predominantly affected. Mechanisms of injury were mainly traffic-related and fall. Orbital injuries were the commonest followed by maxillary injuries. The median and range face abbreviated injury score (AIS) was 2 [1–3] with 66% had a score of 2. Maxillofacial fractures were frequently associated with traumatic brain injuries. One out of five patients was managed with surgery and had median length of stays in ICU and hospital 5 and 7 days, respectively. Overall, in-hospital mortality was 8.3%. Mortality in isolated maxillofacial was low (0.3%) in comparison to 15% in polytrauma patients (p = 0.001). Multivariable regression analysis showed that Injury Severity Score, face AIS and Glasgow Coma Scale were predictors of mortality with age-adjusted odd ratio of 1.15, 2.48 and 0.82; respectively. Conclusions Maxillofacial trauma requiring admission is not uncommon in our trauma center and mostly it is mild to moderate in severity. Associated injuries are present in most of the maxillofacial injured patients and further diagnostic investigations should be part of the assessment in maxillofacial injuries. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00068-019-01174-6